Baltic Sea Gastrotricha—one new species and one new record of Chaetonotida from Poland - Kolicka, Małgorzata; Jankowska, Emilia; Kotwicki, Lech (Zootaxa, 2015)
Gastrotricha is a cosmopolitan phylum of aquatic and semi–aquatic invertebrates that comprise about 820 described species, which are divided into two orders: Chaetonotida Remane, 1925 [Rao & Clausen, 1970] and Macrodasyida Remane, 1925 [Rao & Clausen, 1970]. They inhabit natural as well as artificial habitats in diverse marine, freshwater, and semi–aquatic ecosystems (e.g. peatbogs, alder woods, riparian forests). Until now, 29 species of gastrotrichs from the Polish Baltic Sea region (including three freshwater species which were found in estuaries) were known. Sixteen species belong to Chaetonotida and thirteen to Macrodasyida. During this study we found two species, Heterolepidoderma sinus spec. nov., and Aspidiophorus lamellophorus Balsamo, Hummon, Todaro et Tongiorgi, 1997 which is new to the Baltic Sea fauna. H. sinus spec. nov. has distinct cuticular reinforcements in the anterior dilatation of the pharynx. Moreover, it is characterized by two kinds of lamellae: one type is represented by small triangular lamellae which aris from lateral scales, the second type is large and clearly visible and arises from ventral scales. None of the Heterolepidoderma species known so far has two types of lamellae. A. lamellophorus was previously known only from the Mediterranean Sea. The finding of two new gastrotrich species in the Baltic Sea shows that the knowledge of these small invertebrates in the area is still far from complete.